Effect of almond consumption on insulin sensitivity and serum lipids among Asian Indian adults with overweight and obesity– A randomized controlled trial - Gayathri, Rajagopal; Abirami, Kuzhandhaivelu; Kalpana, Natarajan; Manasa, Valangaiman Sriram; Sudha, Vasudevan; Shobana, Shanmugam; Jeevan, Raman Ganesh; Kavitha, Vasudevan; Parkavi, Karthikeyan; Anjana, Ranjit Mohan; Unnikrishnan, Ranjit; Gokulakrishnan, Kuppan; et al. (Frontiers in Nutrition, 2023)
Background: Asian Indians have an increased susceptibility to type 2 diabetes and premature coronary artery disease. Nuts, like almonds, are rich in unsaturated fat and micronutrients with known health benefits. Objectives: This study aimed to assess the efficacy of almonds for reduction of insulin resistance and improving lipid profile in overweight Asian Indian adults. Methods: This parallel-arm, randomized, controlled trial was conducted in Chennai, India on 400 participants aged 25–65 years with a body mass index ≥23kg/m2. The intervention group received 43g of almonds/day for 12 weeks, while the control group was advised to consume a customary diet but to avoid nuts. Anthropometric, clinical and dietary data were assessed at periodic intervals. Glucose tolerance, serum insulin, glycated haemoglobin, C-peptide and lipid profile were assessed at baseline and end of the study. Insulin resistance (homeostasis assessment model-HOMA IR) and oral insulin disposition index (DIo) were calculated. Results: A total of 352 participants completed the study. Significant improvement was seen in DIo [mean (95% CI) =+0.7 mmol/L (0.1, 1.3); p=0.03], HOMA IR (-0.4 (-0.7, -0.04; p=0.03) and total cholesterol (-5.4 mg/dl (-10.2, -0.6); p=0.03) in the intervention group compared to the control group. Incremental area under the curve (IAUC) and mean amplitude of glycemic excursion (MAGE) assessed using continuous glucose monitoring systems were also significantly lower in the intervention group. Dietary 24-hr recalls showed a higher significant reduction in carbohydrate and increase in mono unsaturated fatty acid (MUFA) and polyunsaturated fatty acids (PUFA) intake in the intervention group compared to the control group. Conclusion: Daily consumption of almonds increased the intake of MUFA with decrease in carbohydrate calories and decreases insulin resistance, improves insulin sensitivity and lowers serum cholesterol in Asian Indians with overweight/obesity. These effects in the long run could aid in reducing the risk of diabetes and other cardiometabolic disease.